ASSESSMENT ON THE FERMENTABILITY OF XYLOOLIGOSACCHARIDES FROM RICE HUSKS - Patricia Gullón; Nuria Salazar; María Jesús González Muñoz; Miguel Gueimonde; Patricia Ruas-Madiedo; Clara G. de los Reyes-Gavilán; Juan Carlos Parajó (BioResources, 2011)
Rice husks were subjected to processing with hot, compressed water under selected conditions to cause the partial breakdown of xylan into soluble products (mainly xylooligosaccharides, XOS). The reaction media were subjected to membrane processing, endoxylanase treatment and ion exchange to obtain purified XOS concentrates. Human fecal slurry cultures with XOS were carried out to assess their bifidogenic activity to stimulate the production of Short Chain Fatty Acids (SCFA) and lactic acid. Results were compared with data obtained in similar cultures containing the prebiotic inulin and the non-prebiotic glucose. The experimental results confirmed the ability of XOS concentrates to act as fermentable carbohydrates for the human colonic microbiota, producing a rapid decrease of pH, comparable to that promoted by glucose and more pronounced than that occurring with inulin. XOS having different DP were degraded at different rates. The experimental results confirmed the ability of rice husk’s XOS concentrates for supporting the growth of bifidobacteria and for acting as carbon sources, leading mainly to the generation of acetic and lactic acids.